2018
DOI: 10.1097/nur.0000000000000356
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Clinical Nurse Specialist Practice in the Implementation of Video Monitoring at an Academic Medical Center

Abstract: Clinical nurse specialists were successful in collaborating with interdisciplinary colleagues to support the development of a Constant Observation Program that included video monitoring. In addition, clinical nurse specialists developed documentation, policies, and procedures to support this new technology. Success was evidenced by support of and growth of the program over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Virtual sitters may continue as a fall prevention strategy, as the literature supports many hospitals experienced encouraging results in terms of fall reduction 6–11. In addition, the cost savings for hospitals that introduced CVM were convincing 6–18…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Virtual sitters may continue as a fall prevention strategy, as the literature supports many hospitals experienced encouraging results in terms of fall reduction 6–11. In addition, the cost savings for hospitals that introduced CVM were convincing 6–18…”
Section: Discussionmentioning
confidence: 99%
“…All studies calculated falls per 1000 patient-days 6. Interestingly, of the 12 studies, only 5 found a decline in the number of falls6–11; however, none of the studies showed an increase in falls 6–18…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Research is limited to highlevel certainty regarding implementation success, for example, utilization of advanced practice nurses to promote interdisciplinary collaboration and the development of successful policy and procedure. 11 However, details on how to sustain and/or expand a program do not exist in the current literature. The next section of this article explains the metrics we used to show the value of CVM in our organization, which allowed for expansion of our program with additional purchase of cameras and expansion of our VMT labor pool.…”
Section: Problemmentioning
confidence: 99%